VISUAL RHETORIC OF ‘GUS’ AS POLITICAL IMAGE: ISLAM-NATIONALIST OR COMMODIFYING ISLAM - Aditya Fahmi Nurwahid; Rahmatillah Dwi Putri (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
The rise of Islam-nationalist ideology in Indonesia's political contestation brings various Muslim figures to be involved. One of the most popular in the 2024 General Election is the appearance of ‘Gus’ as a representation of youth and religious politicians. This research focused on the construction of ‘Gus’ as a political image, and explored how their public relations team used visuals as an essential channel for storytelling, persuading, and image building. Adopting the agenda-setting theories and Burke’s dramatist pentad, this research draws the visual framing, answering ‘what is shown’ to the public and ‘how it is characterized’ as a presentation in social media. This research conducts the qualitative data analysis of four figures: Gus Muhaimin Iskandar, Gus Saifullah Yusuf, Gus Taj Yasin Maimoen, and Gus Ahmad Mudlor Ali. As a result, this research validates that the PR team used socially mediated images to build images based on “Islamic idealism”, the power of a local strongman, the leadership, and the point of view to legitimize their political position. To understand the political visual rhetoric, this research adopted the pentadic reading by looking at the element of social media post. It identifies the commodification goals of every figure, and shows where messaging priorities lies.